1978
DOI: 10.1007/bf00278726
|View full text |Cite
|
Sign up to set email alerts
|

Identity of euchromatic bands from man to Cercopithecidae

Abstract: The karyotypes of four species of Cercopithecidae: Cercopithecus aethiops tantalus, C. sabaeus, Erythrocebus patas, and Miopithecus talapoin are analysed with nearly all the banding techniques. They are compared with each other, and with the karyotypes of the Baboon P. papio and with that of man. It can be concluded that the quasi-totality or the totality of the euchromatin is common to all, but has undergone structural rearrangements, generally detectable. The heterochromatin, defined by C-band staining, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…(c) Pair number 4 with a paracentric inversion in one chromosome observed in a female C. nigrivittatus. the constitutive heterochromatin regions, as has previously been described in the species of the same genus: C. apella (Seuá nez et al, 1986;Freitas and Seuá nez, 1982;Matayoshi et al, 1987;Ponsà et al, 1995;García et al, 2003) and C. capucinus (Dutrillaux et al, 1978;Garcia et al, 1983;Carlà and Stanyon, 1992). In C. apella, previous reports have detected size variation of non-centromeric heterochromatin regions in chromosomes 4, 6, 11, 12, 17, 18 and 19 (Matayoshi et al, 1987;Ponsà et al, 1995).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…(c) Pair number 4 with a paracentric inversion in one chromosome observed in a female C. nigrivittatus. the constitutive heterochromatin regions, as has previously been described in the species of the same genus: C. apella (Seuá nez et al, 1986;Freitas and Seuá nez, 1982;Matayoshi et al, 1987;Ponsà et al, 1995;García et al, 2003) and C. capucinus (Dutrillaux et al, 1978;Garcia et al, 1983;Carlà and Stanyon, 1992). In C. apella, previous reports have detected size variation of non-centromeric heterochromatin regions in chromosomes 4, 6, 11, 12, 17, 18 and 19 (Matayoshi et al, 1987;Ponsà et al, 1995).…”
Section: Resultssupporting
confidence: 57%
“…In Venezuela, C. nigrivittatus is widely distributed and represented by five subspecies (Hershkovitz, 1949;Cabrera, 1957;Bodini and Pé rezHerná ndez, 1987). Chromosome number (2n=52), R-banding and C-banding have been previously described (Dutrillaux et al, 1978;Martinez et al, 1999). Sequential G-/C-banding karyotypes, chromosome homologies among C. nigrivittatus, C. apella and human karyotypes, as well as evolutionary reorganisations that would explain these homologies, were published based upon G-banding comparison and ZOO-FISH results using all human chromosome probes (García et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The karyotypes of the genus Cebus are known to have large heterochromatic segments whose richness in G+C bases suggested by cytogenetic methods (21) was confirmed by using a biochemical analysis (22). Moreover, because a clear analogy exists between the euchromatic material of the chromosomes of Cebus and man (23,24), the comparison of the staining patterns produced by antibodies to Z-DNA in euchromatin may be considered a check of the stability of Z-DNA conformation during chromosome evolution.…”
mentioning
confidence: 96%
“…By in situ hybridization, it has been shown that these heterochromatic segments possess a very repetitive G+C-rich satellite DNA (22). These segments clearly differ from the juxtacentromeric heterochromatin, which is R-, T-, G-, and Q-band negative (21) and for which no information exists concerning G+C richness.…”
mentioning
confidence: 99%